GCM-AES-VR : A Scheme for Cloud Data Confidentiality and Authenticity - Sajjan, Rajani S; Ghorpade, Vijay R (International Journal of Computer Sciences and Engineering, 2018)
Cloud data security is recognized as making the data confidential along with proper authentication. The Galois/Counter Mode (GCM) is used to provide data confidentiality with associated data as authentication. It aims to provide birthday bound security i.e. it is secure up to adversarial queries where is a block size. But in some cases this much security is not sufficient. In this paper, we have proposed a new approach to authenticated encryption with associated data (AEAD), an improved AEAD scheme which can be secure up to approximately adversarial queries where, , where is a block size and is a bit variance. This bit variance is introduced in the encryption process. In the proposed nonce-respecting AEAD scheme a new pseudorandom function is defined and used for implementation. To generate authentication tag universal hash function is used. In this paper security proofs of proposed scheme are given by presenting its construction and its security model.